(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Planktonic foraminiferal microfaunas contained in Pleistocene samples from 60 cores of the L-DGO collection, recovered during several VEMA cruises in che castern North Atlantic Ocean are considered. Cores range in depth from -958 meters to -5755 meters. These samples have been divided into homogeneous groups according to location and bathymetry. Three areas could be recognized with different sedimentological characters. 1) The northern area, between 30° and 21° latitude N, contains samples which are not very disturbed by displacement, so that dissolution of foraminiferal tests is directly correlated to depth. A comparison with the dissolution facies previously defined has been attempted for these samples, where the eolytic and the mesolytic facies can be distinguished, while the alytic facies is absent. 2) The area encompassing the Cape Verde-Madeira and Gambia abyssal plains includes samples from depths in excess of 5000 meters: the pleistolytic and the hololytic facies are represented here. E-W transects of progressively deeper cores point out the relation between depth and dissolution. SEM photographs of the sediment fraction greater than 63 microns document the various dissolution facies identified. 3) The southern area, ranging from 21° to 10° latitude N, is characterized by sediments in which the effects of volcanism, intense displacement and deep cold water upwelling coexist, expecially near Cape Verde, with an increase of siliccous organisms. Dissolution is hidden by resedimentation, which seems to be one of the dominane aspects of this area.